2018
DOI: 10.3846/jcem.2018.6604
|View full text |Cite
|
Sign up to set email alerts
|

Progress in Urban Greenery Mitigation Science – Assessment Methodologies Advanced Technologies and Impact on Cities

Abstract: Urban greenery is a natural solution to cool cities and provide comfort, clean air and significant social, health and economic benefits. This paper aims to present the latest progress on the field of greenery urban mitigation techniques including aspects related to the theoretical and experimental assessment of the greenery cooling potential, the impact on urban vegetation on energy, health and comfort and the acquired knowledge on the best integration of the various types of greenery in the urban frame. Also … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
53
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 134 publications
(72 citation statements)
references
References 306 publications
(387 reference statements)
1
53
0
Order By: Relevance
“…Our findings revealed that vegetation cover generally has the largest strength in shaping the LST patterns at most of the studied scales and lends support to previous argument that the natural surface contributes more to the LST pattern than human activity, and highlight the importance of green vegetation (and nature-based solution) for city planning in the context of climate adaptation [12]. In contrast, some case studies have found that the cooling effect of the water body was better than the green vegetation due to the higher rate of the heat consuming process of transpiration [14,54]. Our results suggest that this is also possible, as for the single-city level, the results of many cities showed that the water body was the dominant factor to explain the LST pattern, especially at finer spatial scales ( Figure 6).…”
Section: Discussionsupporting
confidence: 85%
See 3 more Smart Citations
“…Our findings revealed that vegetation cover generally has the largest strength in shaping the LST patterns at most of the studied scales and lends support to previous argument that the natural surface contributes more to the LST pattern than human activity, and highlight the importance of green vegetation (and nature-based solution) for city planning in the context of climate adaptation [12]. In contrast, some case studies have found that the cooling effect of the water body was better than the green vegetation due to the higher rate of the heat consuming process of transpiration [14,54]. Our results suggest that this is also possible, as for the single-city level, the results of many cities showed that the water body was the dominant factor to explain the LST pattern, especially at finer spatial scales ( Figure 6).…”
Section: Discussionsupporting
confidence: 85%
“…Within each grid cell, we calculated the natural-surface and non-surface variables. Our natural-surface variables included vegetation cover and water cover (seen in Figure A3, Appendix A) as they are the most commonly used variables in the studies of the surface UHI effect [4,14,19,35]. Within each grid cell, we calculated the mean of the normalized difference vegetation index (NDVI) for all vegetated pixels as an indicator of vegetation cover.…”
Section: Natural-surface and Non-surface Variablesmentioning
confidence: 99%
See 2 more Smart Citations
“…Atmosphere 2019, 10, 33 14 of 17 with respect to ventilation and human thermo-physiological conditions. Further, the impact of passive methods [58], including vegetation [59][60][61], as well as lift-up design [62], which are becoming increasingly popular in China to improve the pedestrian level wind and thermal comfort.…”
mentioning
confidence: 99%